MOTIVASI , KOMUNIKASI, LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI PENGARUHNYA TERHADAP KINERJA PEGAWAI NEGERI SIPIL WILAYAH LOWOKWARU - Cholilah Cholilah; Rois Arifin; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT The purpose of this research is useful 1) to prove that employee performance affects motivation, communication, work environment and organizational commitment partially, 2) to know that employee performance influences motivation, communication, work environment and organizational commitment simultaneouslyBy using a sample of 80 civil servants in the Lowokwaru sub-district.Method of collecting data with Systematic Random Sampling       The results of this study indicate that simultaneously variables of motivation, communication, work environment and organizational commitmen significantly influence. Partially motivation and work environment do not significantly influence communication performance and organizational commitmen significantly influence employee performance Keywords: Performance, motivation, communication, work environment and organizational commitmen